Iman Katolik dan Ateis: Sebuah Dialog dengan Ateisme Karl Marx dan Relevansinya bagi Umat Beriman Kristiani - Agustinus Abraham (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
This study discusses the dialogue between Christian faith and Karl Marx’s atheism as well as its relevance to the lives of contemporary Christians. The rise of atheism in modern society is closely related to secularization, scientific progress, social inequality, and criticism of religious institutions that are considered unable to answer humanitarian problems. Karl Marx viewed religion as an ideological instrument that often legitimized oppression and alienated humans from their true existence. Through his famous statement that “religion is the opium of the people,” Marx criticized forms of religiosity that merely comfort human suffering without striving for social liberation. This research employs a qualitative method with a literature review approach by examining various philosophical, theological, and social sources related to Marx’s atheism and the Catholic Church’s teachings. The findings reveal that Marx’s criticism of religion should not merely be understood as a rejection of God, but also as a moral challenge for the Church to continuously renew itself in carrying out its mission amid social realities. In response, the Catholic Church, especially through the teachings of the Second Vatican Council, views atheism not only as a doctrinal challenge but also as an opportunity for dialogue and self-reflection. The study concludes that authentic Christian faith is not an escape from worldly realities but a spiritual force that encourages believers to uphold justice, solidarity, and human dignity. Therefore, Marx’s criticism can become a reflective instrument for Christians to embody a more contextual, humanistic, and socially engaged faith in the modern world.